Electronic Waste and Printed Circuit Board Recycling Technologies - Kaya, Muammer (The Minerals, Metals & Materials Series, 2019)
This book covers state-of-the-art technologies, principles, methods and industrial applications of electronic waste (e-waste) and waste PCB (WPCB) recycling. It focuses on cutting-edge mechanical separation processes and pyro- and hydro-metallurgical treatment methods. De-soldering, selective dismantling, and dry separation methods (including the use of gravity, magnetic and electrostatic techniques) are discussed in detail, noting the patents related to each. The volume discusses the available industrial equipment and plant flowsheets used for WPCB recycling in detail, while addressing potential future directions of the field. This practical, comprehensive, and multidisciplinary reference will appeal to professionals throughout global industrial, academic and government institutions interested in addressing the growing problem of e-waste. Covers principles, methods and industrial applications of e-waste and PCB recycling; Details state-of-the-art mechanical separation processes and pyro- and hydro-metallurgical treatment methods; Describes the available industrial equipment used and plant flowsheets for PCB recycling and addresses potential future developments of this important field.